Oath of Office - Palmer, Michael 1942-2013. (New York : St. Martins Paperbacks, 2013)
"What if a well respected doctor inexplicably goes on a murderous rampage? When Dr. John Merriman goes on a shooting spree at the office, his business partner, staff, and two patients are killed in the bloodbath. Then Meacham turns the gun on himself. The blame falls on Dr. Lou Welcome. Welcome worked with Merriman years before as a counselor after Johns medical license had been revoked for drug addiction. Lou knew that John was an excellent doctor and deserved to be practicing medicine and fought hard for his license to be restored. After hearing the news of the violent outburst, Lou is in shock like everyone else, but mostly hes incredulous. And when he begins to look into it further, the terrifying evidence he finds takes him down a path to an unspeakable conspiracy that seems to lead directly to the White House and those in the highest positions of power"--Provided by publisher.
Includes an excerpt from Political suicide (p. [439]-453).
Keywords: Physicians -- Fiction; Mass murder -- Fiction; Conspiracies -- Fiction; Political corruption -- Fiction; Suspense fiction